PERAN PEREMPUAN INDONESIA DALAM PEMBANGUNAN PERTANIAN (THE ROLE OF THE INDONESIAN WOMAN IN AGRICULTURE DEVELOPMENT) - Farmia, Asih (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2006)
Gender is not identical with sex. We have known that the man and the woman have to separate role and responsibility as the result of culture constructional. The agriculture development which has gender refraction, actually has caused women resources and the young generation are lower than the man resources, so the woman role does not appear, yet. We can see that the man like as though big domination, on the other hand, the woman has role enough, too. It needs respond toward potency, aspiration and problems of the agribusiness subject (both of the man and the woman), so the planning, activities, evaluation and monitoring, and the report of program/ project/ empowering activies of the human resources are responsive toward both of agribusiness subject, except target exact, it has to justness, too, It is needed to increase effectivities and efficiency of development program.